Korelasi antara Tingkat Spiritual dengan Self Regulation pada Lansia di Desa Kebonagung Kecamatan Kraksaan Kabupaten Probolinggo - Junaedi, Achmad; Permatasari, Noer Indah (AS-SABIQUN, 2025)
This study is motivated by the limited research on the relationship between spiritual level and self-regulation among the elderly, despite self-regulation being crucial in helping seniors cope with various life changes and challenges in old age. The objective is to determine the correlation between spiritual level and self-regulation among the elderly in Kebonagung Village, Kraksaan District, Probolinggo Regency. A quantitative analytic cross-sectional design was employed, involving 54 elderly participants selected through simple random sampling. Data were collected via questionnaires and analyzed using Chi-Square and Spearman’s Rho tests. The analysis revealed a p-value of 0.000 (< α = 0.05), indicating a significant correlation between spiritual level and self-regulation in the elderly. It was found that the majority of respondents with low spiritual levels had moderate self-regulation. These results align with theories suggesting that spiritual activities play a role in emotion management and anxiety reduction. The main conclusion is the acceptance of hypothesis H1, confirming a correlation between spiritual level and self-regulation. The implications of this study include enriching the literature on aging and recommendations for government, industry, and academia to develop training, policies, and further studies related to spirituality and self-regulation across different age groups.